Harapan anak usia sekolah penyandang talasemia yang bergantung pada transfusi - Yanti, Silvya Dwi; Mardhiyah, Ai; Hendrawati, Sri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Children with transfusion-dependent thalassemia require lifelong blood transfusion and iron chelation treatment, resulting in stressful conditions that interfere with the child's psychosocial well-being and may lead to hopelessness. Hopelessness leads to loss of hope and non-compliance with treatment. Purpose: To identify the expected picture of school-age children with thalassemia who are dependent on transfusions. Method: This study is a quantitative descriptive study with univariate analysis. This study used a total sampling technique totaling 44 school-age children with transfusion-dependent thalassemia with parents who are POPTI members. This study used the Child Hope Scale instrument which has been translated and has been tested valid and reliable. Results: That the level of expectations of respondents was in the moderate category as many as 29 people (65.9%). Likewise, the pathway dimension as many as 25 people (56.8%) and the agency dimension as many as 28 people (63.6%) are in the moderate category. Conclusion: The expectancy level of children with transfusion-dependent thalassemia is mostly in the moderate category. Suggestion: Future researchers can further examine the influence of hope on children with thalassemia and relate it to other variables such as quality of life or factors related to hope in school-age children with thalassemia who depend on transfusions. Keywords: Children; Hope; School Age; Thalassemia; Transfusion. Pendahuluan: Anak penyandang talasemia yang bergantung pada transfusi membutuhkan pengobatan transfusi darah dan kelasi besi seumur hidupnya sehingga mengalami kondisi stres yang mengganggu psikososial anak dan dapat terjadi keputusasaan. Keputusasaan menyebabkan penyandang kehilangan harapan dan tidak mematuhi pengobatan. Tujuan: Untuk mengidentifikasi gambaran harapan anak usia sekolah penyandang talasemia yang bergantung pada transfusi. Metode: Penelitian deskriptif kuantitatif dengan analisis univariat. Penelitian ini menggunakan teknik total sampling berjumlah 44 anak usia sekolah penyandang talasemia yang bergantung pada transfusi dengan orang tua anggota POPTI. Penelitian ini menggunakan instrumen Child Hope Scale yang sudah diterjemahkan dan sudah teruji valid serta reliabel. Hasil: Tingkat harapan responden berada dalam kategori sedang sebanyak 29 penyandang (65.9%). Begitu pula dimensi pathway sebanyak 25 penyandang (56.8%) dan dimensi agency sebanyak 28 penyandang (63.6%) berada pada kategori sedang. Simpulan: Tingkat harapan anak penyandang talasemia yang bergantung pada transfusi sebagian besar berada dalam kategori sedang. Saran: Bagi peneliti selanjutnya dapat meneliti lebih lanjut mengenai analisis pengaruh harapan pada anak penyandang talasemia dan menghubungkan dengan variabel lainnya seperti kualitas hidup ataupun mengenai faktor-faktor yang berhubungan dengan harapan anak usia sekolah penyandang talasemia yang bergantung pada transfusi.